2007
DOI: 10.1108/17530180200700028
|View full text |Cite
|
Sign up to set email alerts
|

Services for young people with learning disabilities and mental health needs from South Asian communities

Abstract: Children and young people with learning disabilities and mental health problems from black and minority ethnic communities face barriers in accessing services. This paper describes a mapping of services used by young people with learning disabilities and mental health problems from Pakistani and Bangladeshi communities. Overall the participants accessed primary health care services through their GPs, had contact with Social Services for support and benefits and the voluntary sector for culturally appropriate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 6 publications
2
31
1
Order By: Relevance
“…With the exception of two participants, who were no longer living at home, none were dissatisfied with services. This is in contrast with the views of parents from previous research, who have expressed dissatisfaction with services ( Hatton et al, 1998, Hensel et al, 2005and Raghavan & Waseem, 2007.…”
Section: Theme 3 (Sub-theme1): Following and Noticing Rulescontrasting
confidence: 55%
See 3 more Smart Citations
“…With the exception of two participants, who were no longer living at home, none were dissatisfied with services. This is in contrast with the views of parents from previous research, who have expressed dissatisfaction with services ( Hatton et al, 1998, Hensel et al, 2005and Raghavan & Waseem, 2007.…”
Section: Theme 3 (Sub-theme1): Following and Noticing Rulescontrasting
confidence: 55%
“…The majority of the research in this area has focussed on the views of carers (Hatton et al, 1998;McGrother et al, 2002;Raghavan & Waseem, 2007) who report a high level of awareness of health services such as General Practitioners (GPs'), dentists and opticians, but less awareness of specialist services such as community intellectual disability nurses (Hatton et al, 1998;Raghavan & Waseem, 2007). Generally, carers in these studies are reported to be unsatisfied with services.…”
Section: Views Of Care and Supportmentioning
confidence: 99%
See 2 more Smart Citations
“…This contradicts a prevailing belief that people of Pakistani origin hide disability (Raghavan and Waseem 2007). It also underlines not only the familial need for genetic information but also the need in consanguineous communities for interventions at the community level to promote greater understanding of genetics.…”
Section: Discussionmentioning
confidence: 82%